Peran peringkat PROPER dan Biaya Lingkungan terhadap Nilai Perusahaan BUMN di Indonesia - nur ahmad (Jurnal Akuntansi, 2021)
Every companys goal is to make their stock holder prosperous by giving them dividend, capital gain, also the investor will add their money for the company aiming to achieve a better performance. However, as the business grows in the last few years, most company responsible to pay attention more to the environmental impact as the effect of its company activities. This research using saturated sampling technique which sampling technique makes all members of the population sampled. Sample of this research are 20 state-owned corporation (BUMN) that listed in Bursa Efek Indonesia (BEI) during 2013 2017. The type of data used is the secondary data, obtained from www.idx.co.id. The analytical method used in this research is analysis Structural Equation Modeling (SEM) which combine simultaneous system of equations or path analysis. Based on the result shows that environmental performance and environmental costs have a negative effect on firm value.Keywords: Environmental Performnce, Environmental Cost, Firm Value.